Dietary Patterns and Gut Microbiome Composition in a Large Population-Based Cohort - Chen, Zhangling (Curr Dev Nutr, 2020)
OBJECTIVES: Effects of diet on health and disease risk may be mediated by changes in gut microbiome composition. Our aim was to examine associations between intake of food groups and overall diet quality with gut microbiome composition in a large population-based cohort. METHODS: We analyzed data of 1130 participants (median age 57 years) from the Rotterdam Study, a population-based cohort study in the Netherlands. We measured dietary intake using a 389-item FFQ, and assessed adherence to dietary guidelines for 14 food groups and combined into a diet quality score. We assessed gut microbiome composition using 16S rRNA gene sequencing. Data were available for 11 phyla, 19 classes, 25 orders, 44 families, and 184 genera. Alpha diversity was quantified by Shannon index and Richness, and beta diversity was qualified by Bray-Curtis distance. We used linear models to examine associations with Shannon index and Richness, Adonis function to examine variations of Bray-Curtis distance, and Multivariate Association with Linear Models to examine associations with gut microbial communities. Models were adjusted for technical covariates, energy intake, age, sex, physical activity, education, smoking and BMI. RESULTS: After adjustment, higher diet quality was associated with more alpha diversity and explained part of the variation in beta diversity (P < 0.001). Overall diet quality was associated with relative abundance of four families (Erysipelotrichaceae, Ruminococcaceae, Lachnospiraceae, Christensenellaceae), and 15 genera (Torques group, RuminococcaceaeUCG002, RuminococcaceaeUCG003, RuminococcaceaeUCG005, RuminococcaceaeUCG010, Xylanophilum group, Blautia, RuminococcaceaeNK4A214 group, Eligens group, Coprococcus3, Senegalimassilia, Lachnospira, Halliigroup, ChristensenellaceaeR7 group, Ventriosum group) (adjusted p: q < 0.05). Results were not explained by any single food group. Higher intake of fruits, vegetables, whole grains, and tea, and lower intake of red meat and alcohol were all related to microbiome composition. Replication analyses are ongoing. CONCLUSIONS: Better overall diet quality may improve overall gut microbial diversity. Furthermore, diet quality may influence abundance of certain gut microbial communities, several of which have previously been linked to lower risk of metabolic and inflammatory diseases. FUNDING SOURCES: N/A.